Netnographic Insights: Unveiling Green Marketing Strategies for Business Development in Scarlett Cosmetics - Milany, Audy Putri; Santi, Ira Nuriya; Rombe, Elimawaty; Murad, Moh. Ali (Yayasan Riset dan Pengembangan Intelektual, 2025)
In today’s world, both national and international companies are increasingly producing environmentally friendly products and services as part of their Corporate Social Responsibility (CSR) efforts, which positively impact the environment and society. Scarlett Cosmetics is one such company. This study aims to explore the green marketing strategies implemented by Scarlett Cosmetics. A virtual ethnographic approach was employed, utilizing online observation techniques with a